If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Solve + -3(2x + -9) = -3 Reorder the terms: elovS + -3(-9 + 2x) = -3 elovS + (-9 * -3 + 2x * -3) = -3 elovS + (27 + -6x) = -3 Reorder the terms: 27 + elovS + -6x = -3 Solving 27 + elovS + -6x = -3 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + elovS + -27 + -6x = -3 + -27 Reorder the terms: 27 + -27 + elovS + -6x = -3 + -27 Combine like terms: 27 + -27 = 0 0 + elovS + -6x = -3 + -27 elovS + -6x = -3 + -27 Combine like terms: -3 + -27 = -30 elovS + -6x = -30 Add '6x' to each side of the equation. elovS + -6x + 6x = -30 + 6x Combine like terms: -6x + 6x = 0 elovS + 0 = -30 + 6x elovS = -30 + 6x Divide each side by 'lovS'. e = -30l-1o-1v-1S-1 + 6l-1o-1v-1xS-1 Simplifying e = -30l-1o-1v-1S-1 + 6l-1o-1v-1xS-1
| 4x+6y=-132 | | 3-2x=5(3+x) | | 6+2x=2x+6 | | 9n-7=4n+8 | | 10x-50+50=-15+50 | | 23-4x=7-8x | | 12x=18-2x | | -x+1=2x+13 | | -3x-25+15x=8+15 | | -10(v+3)=-25 | | 3(r+4)-6r=-9(-3) | | -2x^2m^2(m^2-4m)= | | x+102=4x | | -7+n=3n+1 | | 75h+10= | | 15+1.50x=45 | | 14=n+8+5n | | 10x-50=-15 | | 1-5v-7v=-11 | | -9-8n=8(-6n+3)+7n | | 15x-50-5x=-15 | | -5x=54 | | 12-5=42 | | 8x-5x=8+3x+6 | | (x+102)=4x | | -24=6(-b-6) | | 59.95=11.99x | | =7x-11y+5x-3y+14-3 | | 7x-5=17-4x | | 39.95+0.45x=59.95+0.35x | | 35m+31=20m-74 | | x+50+80+60=180 |